Diagnostic Characteristics of a Clinical Screening Tool in Combination With Measuring Bedside Lactate Level in Emergency Department Patients With Suspected Sepsis. (24th August 2014) - Singer, Adam J.; Taylor, Merry; Domingo, Anna; Ghazipura, Saad; Khorasonchi, Adam; Thode, Henry C.; Shapiro, Nathan I.; Jang, Timothy
Abstract Background Early identification of sepsis and initiation of aggressive treatment saves lives. However, the diagnosis of sepsis may be delayed in patients without overt deterioration. Clinical screening tools and lactate levels may help identify sepsis patients at risk for adverse outcomes. Objectives The objective was to determine the diagnostic characteristics of a clinical screening tool in combination with measuring early bedside point‐of‐care (POC) lactate levels in emergency department (ED) patients with suspected sepsis. Methods This was a prospective, observational study set at a suburban academic ED with an annual census of 90, 000. A convenience sample of adult ED patients with suspected infection were screened with a sepsis screening tool for the presence of at least one of the following: temperature greater than 38°C or less than 36°C, heart rate greater than 90 beats/min, respiratory rate greater than 20 breaths/min, or altered mental status. Patients meeting criteria had bedside POC lactate testing following triage, which was immediately reported to the treating physician if ≥2.0 mmol/L. Demographic and clinical information, including lactate levels, ED interventions, and final diagnosis, were recorded. Outcomes included presence or absence of sepsis using the American College of Chest Physicians/Society of Critical Care Medicine consensus conference definitions and intensive care unit (ICU) admissions, use of vasopressors, and mortality. Diagnostic test characteristics were calculated using 2‐by‐2 tables with their 95% confidence intervals (CIs). The association between bedside lactate and ICU admissions, use of vasopressors, and mortality was determined using logistic regression. Results A total of 258 patients were screened for sepsis. Their mean (± standard deviation [SD]) age was 64 (±19) years; 46% were female, and 82% were white. Lactate levels were 2.0 mmol/L or greater in 80 (31%) patients. Patients were confirmed to meet sepsis criteria in 208 patients (81%). The diagnostic characteristics for sepsis of the combined clinical screening tool and bedside lactates were sensitivity 34% (95% CI = 28% to 41%), specificity 82% (95% CI = 69% to 90%), positive predictive value 89% (95% CI = 80% to 94%), and negative predictive value 23% (95% CI = 17% to 30%). Bedside lactate levels were associated with sepsis severity (p < 0.001), ICU admission (odds ratio [OR] = 2.01; 95% CI = 1.53 to 2.63), and need for vasopressors (OR = 1.54; 95% CI = 1.13 to 2.12). Conclusions Use of a clinical screening tool in combination with early bedside POC lactates has moderate to good specificity but low sensitivity in adult ED patients with suspected sepsis. Elevated bedside lactate levels are associated with poor outcomes.